Effect Of Sodium Chloride Concentrations On Some Of Growth Parameters To Three Genotype Of BarleyHordium vulgare L.) ( - ALSaedi, A . J .H .; Waseen, Sh.M.; AL-Mofty, Z.A.; AL-Hassan, A.K.Abd (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The experiment was carried out in the green house of, Biology Department of ,College of Education , Ibn Al-Haitham , Baghdad University. For growth season 2008-2009 via planting seeds of three genotypes of barley cultivars Baraka , Becson and Baraka x Forest ,to study the effect of different concentrations of NaCl (o , 50 ,100 , 150 , 200 ) mM.L on some growth parameters such as fresh and dry weight of shoot and elements plants the experiment carried out by using completely randomized design applied with four replicates . Data were statistically analyzed by using least significant differenceat0.05probabilitylevel. The results showed that an increase in NaCl salt concentrations from 0 to 200mM.L-1 leads to significant decrease in the some of parameters values with significant increase in sodium and chloride concentrations in the shoot .Moreover the results revealed significant difference among genotypes in their tolerance to high concentrations of NaCl The Barak genotype exhibited a good tolerance against high concentrations of salt.